Eye care delivery models to improve access to eye care for Indigenous people in high-income countries: protocol for a scoping review - Matire Harwood; Jacqueline Ramke; Helen Burn; Joanna Black; Iris Gordon; Anthea M Burnett; Lisa Marie Hamm; Jennifer Evans (BMJ Open)
Introduction Globally, there are an estimated 370 million Indigenous people across 90 countries. Indigenous people experience worse health compared with non-Indigenous people, including higher rates of avoidable visual impairment. Countries such as Australia and Canada have service delivery models aimed at improving access to eye care for Indigenous people. We will conduct a scoping review to identify and summarise these service delivery models to improve access to eye care for Indigenous people in high-income countries.Methods and analysis An information specialist will conduct searches on MEDLINE, Embase and Global Health. All databases will be searched from their inception date with no language limits used. We will search the grey literature via websites of relevant government and service provider agencies. Field experts will be contacted to identify additional articles, and reference lists of relevant articles will be searched. All quantitative and qualitative study designs will be eligible if they describe a model of eye care service delivery aimed at Indigenous populations. Two reviewers will independently screen titles, abstracts and full-text articles; and complete data extraction. For each service delivery model, we will extract data on the context, inputs, outputs, Indigenous engagement and enabling health system functions. Where models were evaluated, we will extract details. We will summarise findings using descriptive statistics and thematic analysis.Ethics and dissemination Ethical approval is not required, as our review will include published and publicly accessible data. This review is part of a project to improve access to eye care services for Māori in Aotearoa New Zealand. The findings will be useful to policymakers, health service managers and clinicians responsible for eye care services in New Zealand, and other high-income countries with Indigenous populations. We will publish our findings in a peer-reviewed journal and develop an accessible summary of results for website posting and stakeholder meetings.